An Analysis of the Professional Development Path of British Community Educators from the Perspective of Professional Jurisdiction - Xiaohan Ye (Adult Education Research Conference, 2023)
This paper adopted the theoretical framework of professional jurisdiction is adopted to presents a picture of the professional evolution of community educators in the UK.
Keywords: community education; community educator; professional jurisdiction; professional development